2018
DOI: 10.1016/j.conbuildmat.2018.01.130
|View full text |Cite
|
Sign up to set email alerts
|

Multiple recycled aggregate properties analysed by X-ray microtomography

Abstract: The increasing production of construction and demolition waste (C&DW) and the ever-greater consumption of natural resources is forcing society to search for alternatives in order to reduce both. Fortunately, many studies have analysed the possibility of producing recycled aggregates (RA) using old concrete from C&DW [1-6], precast industries [7-10] and industry wastes [11-13]. However, the use of RA against the use of natural aggregate (NA) for structural concrete on material performance, environmental benefit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 82 publications
(28 citation statements)
references
References 30 publications
0
21
0
2
Order By: Relevance
“…Traditionally open porosity has been obtained by water saturation, although saturation is a slow process and is influenced by the size and shape of the specimens. Modern methods such as microtomography (Thomas et al, 2018) allow access to the open and close porous network without affecting the material but only in very small samples. In addition, image analysis by backscattered electron images of polished sections were used to characterize the concrete (Hu, 2004, Lange et al, 1994.…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally open porosity has been obtained by water saturation, although saturation is a slow process and is influenced by the size and shape of the specimens. Modern methods such as microtomography (Thomas et al, 2018) allow access to the open and close porous network without affecting the material but only in very small samples. In addition, image analysis by backscattered electron images of polished sections were used to characterize the concrete (Hu, 2004, Lange et al, 1994.…”
Section: Introductionmentioning
confidence: 99%
“…It is also known that the use of CRA but also the new cement paste affect the fatigue behaviour of concrete, reducing the fatigue limit and fatigue life [40,41]. Other authors have shown that the multi-recycling of the concrete that contain CRA is limited and that after three recycling cycles, CRA are mostly composed of mortar and new NA are needed in the mix design [42].…”
Section: Introductionmentioning
confidence: 99%
“…Innovative techniques, such as micro computed tomography (micro- CT) have also been used to analyze the behavior of concrete at fatigue, both in compressive fatigue [12] and bending fatigue [17]. Moreover, some micro-CT studies, which is a technique able to analyse the pores and cracks on concrete [18,19], had been developed to understand the concrete damage fatigue micromechanism [20,21]. In general, fatigue is known to lead to microcracks in concrete growing at lower loads than in static tests, which can lead to concrete failure earlier than expected [22].…”
Section: Introductionmentioning
confidence: 99%